Extensive reading and viewing as input for academic vocabulary: A large-scale vocabulary profile coverage study of students’ reading and writing across multiple secondary school subjects - Green, Clarence (Lingua, 2020)
•Extensive reading and extensive vocabulary coverage computed over 5 subject areas.•Pedagogies provide excellent coverage for productive vocabulary in English a subject.•Consistently high coverage found for science subjects at secondary school.•Coverage higher for students’ productive use in subject area writing than reading.•1/10 to 1/20 words in science subjects still need to come from additional pedagogy. The extent to which extensive reading (ER) and extensive viewing (EV) support academic literacy in secondary school, particularly for L2 students, through relevant vocabulary input has yet to be established. This study undertakes a lexical profile coverage study providing information on how much coverage is afforded by ER/EV vocabulary constructs for reading and writing in biology, physics, chemistry, mathematics and English (as a subject area). It operationalizes ER/EV as vocabulary input constructs through corpora representing general fiction, science fiction, juvenile fiction, television and movies. It computes coverage provided by this input at different frequency bands (e.g. ER/EV's 1st 1000 most frequent word families, 2nd 1000 etc.) in secondary school textbooks and student writing. It finds ER/EV input appears very valuable for English as a subject area, and provides within the first 11–12,000 most frequent word families substantial coverage of receptive and productive vocabulary in secondary school science. Science-fiction provides more coverage, and juvenile fiction less. EV does not appear to offer impoverished coverage to ER. The study suggests that additional vocabulary pedagogy is nevertheless going to be needed, to cover from about 1 in 10 to 1 in 20 vocabulary items in the target subject areas.